Methods of Implementing PR Campaigns for Children's Recreation and Tourism at the Federal and Regional Levels - FEDYUNIN, Dmitry Valerievich; BEZPALOV, Valery Vasilyevich; LOCHAN, Sergey Alexandrovich; GOLOVINA, Vera Viktorovna; KARPOVA, Natalia Dmitrievna (Journal of Environmental Management and Tourism; Vol 9 No 8 (2018): JEMT Volume IX Issue 8(32) Winter 2018DO - 10.14505//jemt.v9.8(32).13, 2019)
PR technologies include marketing research and development of the resulting strategy and program for marketing activities, which are used to improve the business performance and the effectiveness of addressing the needs of the end user or customer. The purpose of this study is to examine the possibilities of using PR in the tourism business, of laying the foundation for competitive and economically sustainable activities, which will improve not only the economic, political, cultural and social state of the tourist region, but also the authority of the Russian tourism industry in the international scene. The study uses the methods of image formation, branding, and evaluating the effectiveness of PR activities. The major outcome of this study is that PR technologies help to develop a positive image of an enterprise since the brand and its credibility are essential in the field of children's recreation and tourism. PR campaigns are designed to create customer interest in the product and to establish partnerships with the colleagues. Conclusions. In the development of children's tourism, as in the development of any other product, special attention should be paid to its information management. To date, based on the target audiences, PR campaigns in the field of children's leisure and tourism are divided into campaigns maintaining relationships with the loyal customers and those attracting new customers. This circumstance requires the selection and rational application of methods and mechanisms to access the effectiveness of these activities.